History and development of Usul Fiqh - Maulidia, Arin Nafisa (Maliki Interdisciplinary Journal, 2024)
This study is disrupted by many problems in the present age that can be solved with the Quran and the Sunnah. On the other hand, the doctrine of ushul fikih can be a solution to the law that is not in the Qur’an and the Sunna. By taking ushul fikih science as an object, this journal focuses on discussing the history and development of ushul fikih. A journal is book or written document that includes the observations, analysis, and ideas of an individual or group of people in a particular field. The findings obtained in this study are: First, in the history and development of the fictional ushul are divided into three periods, i.e., sahabat, tabi’in, and imam madzhab. Second, the currents in the Fictional Ushul are split into three: Asy-Syafi’iyah, Hanafiyah, and Combination. Third, Each one of these streams has a standard book in the fictitious ushul.